Plac Czerwony jako technologia oporu w rosyjskiej sztuce protestu - Dynda, Barbara (Śląskie Studia Polonistyczne, 2020)
Red Square is a symbolic place for the Moscow dissidence protests. Russian artists, writers and dissidents have frequently used the history of the square’s memory as a crucial and fundamental issue within the framework of their strategy. Haunting images associated with Red Square’s past, permanently returning in the history of the Russian activism, always refer both to universal narratives of the politics of protest and to the specific contexts producing entirely new meanings. Each time, through their public actions artists create new meanings for the Red Square’s space – they expose the existing limits of the power apparatus and call for the right to legitimize it, therefore contesting the links between the theatre of legitimacy and the public space. From this perspective, the space of protest becomes a fundamental instrument of political action, and the square - ordinarily used in the established order to manifest the government’s symbolic authority - this time becomes a kind of technique as well as a material body support in the politics of resistance.